Vridsløselille Statsfængsel set i fangeperspektiv - Torkil Lauesen (Nordisk Tidsskrift for Kriminalvidenskab)
This article outlines a study done by an inmate at the Vridsløselille State Prison (Lauesen 1998). Power relations within the prison are contemplated within a Foucaultian conception of power: Power techniques and strategies are characterised, and their consequences examined. Various forms of counter-power-techniques and strategies developed by prisoners in response to the prison environment are also outlined. The consequences of this interaction are conceptualised as "de-socialisation " and "learned helplessness." The article goes on to critique traditional discussions of the negative role of "strong" prisoners, as well as a new prison structure in which the guards perform additional duties as social advisers and pedagogues.